The linkage of perceived neighbourhood environmental safety with travel-time and leisure-time physical activity in adults - Lim, Noor Hashimah Hashim; Jamaluddin, Rosita; Majid, M. Rafee; Tsong, Teh Bor; Abidin, Nurdiyana Zainal; Hasnan, Liyana; Hassan, Linda Shafarina (Faculty of Medicine, Universitas Trisakti, 2024)
Background Having the highest obesity prevalence and physical inactivity among its South East Asian counterparts, it is important for Malaysia to understand the factors contributing to this epidemic. Because low neighbourhood safety is linked to physical inactivity, the objective of this study was to explore perceived neighbourhood safety from traffic and crime with its effects on adults’ travel- and leisure-time physical activities. Methods This cross-sectional study was conducted on 256 adults. Six items on a 4-point Likert scale from the Neighbourhood Environment Walkability Scale (NEWS) and WHO’s GPAQ questionnaires to record weekly minutes of physical activity were used to measure the variables. Forty-three neighbourhoods from Johor Bahru district were categorised into higher and lower socio-economic status by median housing price per square feet. Structural equation modelling (SEM) was used to analyse the data. Results Among 256 adults, males were found to be more physically active than females. SEM showed that for every 1 unit increase in neighbourhood socioeconomic status, males’ perceived neighbourhood environmental safety increases by 0.23 unit (p=0.006); however, this does not explain their physical activities. For the females, regardless of neighbourhood socioeconomic status, every 1 unit increase in perceived neighbourhood environmental safety from traffic and crime encourages physical activity to increase by 0.47 unit (p=0.006), especially for leisure purposes. Both genders perceived that street lighting at night and pedestrian visibility are important safety features of the neighbourhood environment. Conclusion The study outcomes facilitate understanding of causal factors of physical activity through perceived neighbourhood environmental safety, especially among females. Keywords: Neighbourhood environment safety, neighbourhood socioeconomic status, physical activity, gender, adult